Economic Sustainability and Intergenerational Fairness: A New Taxonomy of Indicators - Róbert I. Gál; Judit Monostori (Intergenerational Justice Review)
The aim of this paper is to facilitate informed choice about indicators of economic sustainability and intergenerational fairness and decisions about their uses. We focus on four issues. First, we found that the same type of indicator measured at different levels – such as the general government, the (market) economy or the total economy, which includes both the market economy and the household economy – often leads to different conclusions. Second, sustainability analysis is frequently built on exogenously set age limits even though it is obvious that old age does not everywhere start at age 65; it did not always start there where it does today; and most likely it will not start there in the future. Third, we use our taxonomy of more than 80 indicators to spot holes, shortcomings and absences. Fourth, we show some structural differences between indicators of sustainability and fairness.